2022
DOI: 10.1177/01492063221108921
|View full text |Cite
|
Sign up to set email alerts
|

Quits Versus Discharges Across Job Levels: Revisiting the Positive Side of Turnover

Abstract: Although the functional effects of turnover have been argued from the earliest research in the field, empirical evidence so far supports a general negative effect on unit performance, and attempts to explore its potential benefits are scarce. It has been argued that one reason for the absence of positive effects has to do with a lack of specificity of the turnover construct. The present study focuses on two sources of specificity: the reason for turnover and the job level of the departing employees. Our object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 115 publications
(341 reference statements)
0
1
0
Order By: Relevance
“…Yet another theoretical alternative predicts that low-to-medium turnover could benefit performance by revitalizing the workforce, but high turnover is more costly and less beneficial. This prediction corresponds to an inverted quadratic U-shape (饾憥 1 > 0, 饾憥 2 < 0) found in 35 out of 156 TPR studies surveyed in Hancock et al (2017) (Table 3) and later in De Stefano et al (2019); DeWinne et al (2019); Sim贸n et al (2022), and in Li et al (2022). 2 However, a quadratic U-shape is simply an empirically convenient approximation of a generally nonlinear TPR whose pattern is determined by co-variation in the costs and benefits of turnover with its level.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Yet another theoretical alternative predicts that low-to-medium turnover could benefit performance by revitalizing the workforce, but high turnover is more costly and less beneficial. This prediction corresponds to an inverted quadratic U-shape (饾憥 1 > 0, 饾憥 2 < 0) found in 35 out of 156 TPR studies surveyed in Hancock et al (2017) (Table 3) and later in De Stefano et al (2019); DeWinne et al (2019); Sim贸n et al (2022), and in Li et al (2022). 2 However, a quadratic U-shape is simply an empirically convenient approximation of a generally nonlinear TPR whose pattern is determined by co-variation in the costs and benefits of turnover with its level.…”
Section: Introductionmentioning
confidence: 81%
“…We consider controls for workplace size, workplace-and time-specific fixed effects, and past performance essential. Past performance accounts for past shocks that may have influenced turnover decisions and whose consequences may persist over several periods of time, which is particularly important for relatively high-frequency (quarterly or monthly) observations used in recent TPR studies (De Stefano et al, 2019;Sim贸n et al, 2022) as well as ours. Workplace size controls for the scale of operations which clearly affects output and may also be related to turnover.…”
Section: Controlsmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes consequences for the firm the group departed, the firm(s) its members join, and the departing group itself鈥攂oth collectively and individually. Although some research has discussed turnover鈥檚 potential functional and adaptive nature (Dalton et al, 1982; Sim贸n et al, 2022; Wiersema & Bantel, 1993), most has focused on its adverse effects, such as the greater organizational risk of successive quitting versus that of dispersed departures (Agarwal et al, 2016; Call et al, 2015; Mawdsley & Somaya, 2016; Wezel et al, 2006). Some has even speculated that in times of impending turnover, exiting groups may behave opportunistically by withholding work contributions until joining the new firm (膶erne et al, 2014; Connelly et al, 2012).…”
Section: Future Agendamentioning
confidence: 99%
“…A study conducted in China (Knechel et al, 2021) revealed a decline in audit quality for clients remaining with firms after proficient auditors had moved to more prestigious companies. While the introduction of new perspectives through employee turnover can be beneficial, prevailing views in the audit sector suggest that resignations detrimentally affect effectiveness and compromise the quality of the product (Sim贸n et al, 2023). Interviews with auditors highlighted that high staff turnover leads to shortages, resulting in increased workload pressure, which in turn exacerbates staff turnover.…”
Section: Introductionmentioning
confidence: 99%